1999
DOI: 10.1159/000008622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Distal Anastomotic Intimal Hyperplasia: An Experimental Comparison by Arteriography, Duplex Sonography, Angioscopy, and Intravascular Ultrasound

Abstract: Routine follow-up investigation methods after peripheral arterial bypass surgery, such as arteriography and colour duplex sonography, do not always allow correct analysis of moderate alterations in the vessel wall, e.g. initial stages of distal anastomotic intimal hyperplasia (DAIH). The aim of this study was to evaluate the efficiency of angioscopy and intravascular ultrasound compared to the named routine methods regarding detection of early DAIH. Eight months after bilateral femoropopliteal bypass surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Gunen et al [9] examined intimal hyperplasia associated with experimental vascular anastomosis with angioscopy and IVUS, and reported that the sensitivity in identifying 550 # m-thick intimal hyperplasia was 88% for angioscopy and 100% for IVUS. This suggests the predominance of IVUS in identifying intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Gunen et al [9] examined intimal hyperplasia associated with experimental vascular anastomosis with angioscopy and IVUS, and reported that the sensitivity in identifying 550 # m-thick intimal hyperplasia was 88% for angioscopy and 100% for IVUS. This suggests the predominance of IVUS in identifying intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%